The impact of demographic factors of the population of hotspots on crime in the UAE Society: Emirate of Sharjah as a Model - Beyat, Saud; Alomosh, Ahmed; Altaii, Alaa (Al-Adab Journal, 2024)
The study aims to identify the concept of crime and hot spots and to identify the classification of crimes in the United Arab Emirates and what is its impact on the society of the Emirate of Sharjah. It shows the nature of the relationship between crime and hot spots and what dangers they pose to society. Presenting results, solutions and proposals that enable the security services and the Sharjah Police General Command to work on them to control hot spots and protect society from them. To achieve the objectives of the study, the analytical descriptive approach was used, using the questionnaire as a tool for the study, and it consists of (39) items distributed on four dimensions. The study sample consisted of (507) people who were chosen randomly. The results showed a clear effect of the personal variables represented in the area of residence, the nature of presence, gender and nationality on the four axes of the study: the sense of security, the seriousness of crime, the impact on business, and ways to address crimes. The study reached a number of recommendations, the most important of which are: intensifying efforts related to reducing crimes committed in hot spots, as well as the importance of having cameras in the streets and public places, and the presence of an advanced electronic system in public places for surveillance purposes, as well as the availability of sufficient lighting in places of residence and work, and then developing security initiatives. Innovative to reduce crime in order to confront crimes in hot spots.